Fish-associated Streptococcus agalactiae ST283: first human cases reported from Malaysia - Zohari, Zahira; Barkham, Timothy; Mohamad Maswan, Norfarhana; Swaine, Lin Chen; Muthanna, Abdulrahman; Kai, Wei Lee; Mohd Desa, Mohd Nasir; Azmai, Mohammad Noor Amal; Sither Joseph, Narcisse Mary; Amin-Nordin, Syafinaz (Microbiology Society, 2023)
In South East Asia. Streptococcus agalactiae ST283 causes sepsis in healthy adults. Raw freshwater fish consumption is the only known risk factor. These two case reports are the first from Malaysia. Although they cluster with Singapore ST283, the epidemiology is complicated by the flow of people and fish across borders.